Educação ambiental e coleta seletiva em Presidente Prudente-SP: avaliando seus resultados no Conjunto Habitacional Ana Jacinta - Cantóia, Sílvia Fernanda [UNESP] (2007)
To achieve the proposals of methodology, this research had as basis the project of public policies Enviromental Education and integrated managment of the solid residues in Presidente Prudente-SP: development of methodologies for selected collection, garbage usage and work organization, which started in 2001 ending in 2005, being carried out in partnership by FCT/Unesp, Town Hall of Presidente Prudente, Presidente Prudente's Development Company and other public and private institutions, with FAPESP support. It was aimed to evaluate the results of the public policies project and its impacts in the community education and in the selected collection of recyclabe and reusable residues of the Inhabitated Complex Ana Jacinta, where about 20.000 people live, intending to contribute to the theorical-methodological debate of how to give effectviness to actions of enviromental education and selected collection in partnership with the Public Bureau, public institutions, schools and civil bodies. The achieved methodological procedures were: attendance of the actions of the public policies project, selected collection in the district; analisys of the types and composition of the collected residues; and interviews with the district's population to identify its participation and obtain information that could guide actions for the collection expansion in town. The research also tried to analys e the educational role of the State-owned School Francisco Pessoa as a producer and transmitter agent of information in the process of social engagement of the district towards enviromental topics and its stillness in relation to the educational campaigns in the district and in the school.